Coronary Artery Disease: Optimal Lipoprotein(a) for Survival—Lower Is Better? A Large Cohort With 43,647 Patients - Liu, Jin; Liu, Liwei; Wang, Bo; Chen, Shiqun; Liu, Buyun; Liang, Jingjing; Huang, Haozhang; Li, Qiang; Lun, Zhubin; Ying, Ming; Chen, Guanzhong; Huang, Zhidong; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background High level of lipoprotein(a) would lead to a high risk of cardiovascular events or mortality. However, the association of moderately elevated lipoprotein(a) levels (≥15 mg/dL) with long-term prognosis among patients with coronary artery disease (CAD) was still uncertain. We systematically analysed the relevance of baseline plasma lipoprotein(a) levels to long-term mortality in a large cohort of CAD patients. Methods We obtained data from 43,647 patients who were diagnosed with CAD and had follow-up information from January 2007 to December 2018. The patients were divided into 2 groups (<15 mg/dL and ≥15mg/dL). The primary endpoint was long-term all-cause death. Kaplan-Meier curve analysis and Cox proportional hazards models were used to investigate the association between moderately elevated baseline lipoprotein(a) levels (≥15 mg/dL) and long-term all-cause mortality. Results During a median follow-up of 5.04 years, 3,941(18.1%) patients died. We observed a linear association between lipoprotein(a) levels and long-term all-cause mortality. Compared with lipoprotein(a) concentrations < 15 mg/dL, lipoprotein(a) ≥15 mg/dL was associated with a significantly higher risk of all-cause mortality, (adjusted hazard ratio [aHR] 1.10, 95% CI:1.04-1.16, P values=0.001). Similar results were found for the subgroup analysis of non-acute myocardial infarction, non-percutaneous coronary intervention, chronic heart failure, diabetes mellitus or non-chronic kidney diseases. Conclusion Moderately elevated baseline plasma lipoprotein(a) levels (≥15 mg/dL) were significantly associated with higher all-cause mortality in patients with CAD. Our finding provides a rationale for testing the lipoprotein(a)-reducing hypothesis with lower targets (even <15 mg/dL) in CAD outcome trials.